Phosphoinositide-3-Kinase Inhibition Enhances Radiosensitization of Cervical Cancer In Vivo. Issue 1 (1st January 2011) - Liu, Yi; Cui, Baoxia; Qiao, Yunbo; Zhang, Yan; Tian, Yongju; Jiang, Jie; Ma, Daoxin; Kong, Beihua
Abstract : Background: Phosphoinositide-3-kinase (PI3K)/Akt pathway is downregulated in several human cancers, and PI3K inhibition can sensitize these cancer cells to radiation. However, no research on cervical cancer in vivo has been reported. The present study further investigated whether PI3K inhibition could sensitize cervical cancer to radiation in vivo. Methods: HeLa cells with sustained PI3K activity and Akt phosphorylation were injected subcutaneously into BALB/C nude mice to establish tumor cell xenograft, which were randomly assigned to control, PI3K inhibitor LY294002 alone, radiation alone, or combined LY294002 and radiation group. Akt phosphorylation was detected by Western blotting to evaluate the blocking efficiency on PI3K activity. The radiosensitization of PI3K inhibition was measured by clonogenic assays, apoptosis analysis, and tumor regrowth assays. Results: The combination of LY294002 and radiation resulted in significant and synergistic suppression of cervical cancer cells in a dose-dependent manner in clonogenic assays ( P < 0.05), higher ratio of apoptosis cells, and more remarkable reduction of Akt phosphorylation. Tumor regrowth delay curve showed the lowest increase of tumor volume in the combined group (37 days in average) ( P = 0.003). Besides, LY294002 (100 mg/kg) alone decreased cell survival and produced xenograft regrowth delay. Conclusions: Phosphoinositide-3-kinase inhibition by LY294002 can synergistically enhance radiation efficacy via dephosphorylation of Akt in cervical cancer, and PI3K inhibition alone can also suppress tumor regrowth. This may provide novel therapeutic opportunities to enhance the effect of radiotherapy against cervical cancer.